Linking perceived and actual drinking water quality across rural landscapes of northern Kazakhstan - Nugmanov, Askar; Beisenova, Raikhan; Kali, Almagul; Zhupysheva, Aktoty; Shamshidin, Innar; Beisenova, Danagul (Frontiers in Environmental Science, 2026)
Access to safe drinking water in rural areas remains a global challenge, particularly where decentralized supply systems are common and water quality is highly variable. In this study, we analyze the relationship between the chemical composition of drinking water and community perceptions of its quality in rural settlements of the Akmola Region of Kazakhstan across different landscape types. Using a mixed-methods approach, hydrochemical analyses of household water samples were conducted, ANOVA and Spearman correlation tests were applied, and village-level survey data were collected to assess the complaints, satisfaction, and water purification practices of residents. Results indicate that most water sources are of Ca–Mg–Cl–HCO3 type, with steppe villages showing higher levels of dissatisfaction. These findings highlight the importance of aligning technical water assessments with local perceptions to improve rural water governance and foster community trust in water safety initiatives.